The concept of cyberspace in international law - K. A. Ivanova; M. Zh. Myltykbaev; D. D. Shtodina (Правоприменение, 2022)
The subject. The article is devoted to the analysis of approaches in the development of the concept of cyberspace in international law.The purpose of this article is to try to highlight the attributes of cyberspace, which will allow to resolve existing gaps in the field of universal cyber regulation in international law. The research presented in this article was conducted by combining various disciplinary approaches, including comparative law, comparative politics and international relations, political theory, and sociology. In addition, the study includes methods of dialectical logic, analysis and synthesis, as well as a formal-legal analysis of UN international legal acts.The main results and scope of their application. As states pay increasing attention to cyberspace management as the technical architecture that powers the global Internet and governance in cyberspace, in terms of how states, corporations and users can use this technology, the role of international law in cyberspace is increasing, becoming more prominent, becoming more important. At the same time, note that international law has no specific rules for regulating cyberspace. Moreover, the technology is both new and dynamic. Thus, for several years there have been open questions as to whether existing international law applies at all to cyberspace. Cyberspace is now the backbone of global commerce, communication and defense systems, and is a key aspect of the critical infrastructure that sustains our modern civilization. Technology and information spread almost instantaneously, and the global economy and supply chains are integrated to a degree unprecedented in history. Nevertheless, there is still no developed universal concept of cyberspace in international law, only approaches at the level of the UN, international organizations, including the First Committee of the UN General Assembly on Disarmament and International Security, the G20, the European Union, the Association of Southeast Asian Nations and the Organization of American States and doctrinal approaches are singled out.Conclusions. The competition for strategic technology and the competition for advantage in the "information space" is growing, so far without the standard international rules of the road. Moreover, the future is likely to prove even more transformational. The potential threats are also extraordinary: autonomous weapons, cyber warfare, sophisticated disinformation campaigns and geopolitical instability. In such circumstances, it is crucial to develop a universal notion of cyberspace because of the persistent significant vulnerabilities and number of threats in global communications.